The Use of Dual Energy X-Ray Bone Density Scan in Assessment of Alveolar Cleft Grafting Using Bone Marrow Stem Cells Concentrate/Platelet-Rich Fibrin Regenerative Technique. Issue 8 (November 2021) - Mossaad, Aida M.; Ahmady, Hatem H. Al; Ghanem, Wael H.; Abdelrahman, Moustapha A.; Abdelazim, Ahmed F.; Elsayed, Shadia A.
Abstract : Objectives: To determine the densitometric quality of regenerated bone at the site of bone marrow and platelet-rich membrane grafting technique at unilateral alveolar cleft region using dual energy x-ray bone density scan (DEXA). Methods: The present prospective cohort study included 16 unilateral alveolar cleft patients who were selected randomly from the outpatient maxillofacial surgery clinic and suffered from unilateral alveolar cleft. Bone marrow aspirate and platelet-rich fibrin (PRF) (bone marrow stem cells + PRF) were used as the grafting material. Six months of follow-up have been conducted for all patients' including clinical and radiographic assessments with (DEXA scan). Results: Sixteen unilateral patients with a mean age of 12.56 ± 1.71 years were included in the sample and the majority of patients were females with a frequency of 56.2 percent. The current research revealed no infection or wound dehiscence. After surgery, the pain and edema scores were reasonable. Our findings showed that, after 6 months of regenerative graft, the average bone mineral density of the cleft side DEXA scan value was 1.56 ± 0.32 gm/cm 2, compared to 1.51 ± 0.488 gm/cm 2 on the normal side of the noncleft scan. There was no statistically significant difference in DEXA bone mineral content measurements between the cleft and standard sides ( P = 0.461). Conclusions: The bone marrow stem cells + PRF regenerative graft technique has been successfully integrated, and the DEXA scan approach for measuring regenerated grafted bone mineral content was found to be appropriate for simple and inexpensive follow-up of alveolar cleft lip patients. Abstract : Supplemental Digital Content is available in the text